Case Report: Organizing pneumonia associated with AQP4-antibody neuromyelitis optica spectrum disorder in children - Zhang, Lijun; Liu, Yixuan; Wang, Yakun; Tian, Liyuan (Frontiers in Pediatrics, 2026)
BackgroundAquaporin-4-antibody Neuromyelitis Optica Spectrum Disorder (AQP4-Ab NMOSD) is an immune-mediated inflammatory disorder of the central nervous system, characterized by predominant involvement of the optic nerves and spinal cord. Pulmonary involvement, particularly in the form of organizing pneumonia, remains an uncommon manifestation of AQP4-Ab NMOSD.Case summaryWe present the case of an 8-year-old girl with AQP4-Ab NMOSD who developed organizing pneumonia concurrent with the onset of her neurological disease. The initial lung injury resolved following immunotherapy, while the subsequent injury improved spontaneously. Anti-AQP4-IgG Antibody was detected positive in the bronchoalveolar lavage fluid.ConclusionWhen lung injury occurs in patients with AQP4-Ab NMOSD, detection of anti-AQP4-IgG antibodies in bronchoalveolar lavage fluid may serve as an adjunctive diagnostic tool for the organizing pneumonia associated with AQP4-Ab NMOSD.